Quand la presse locale s’efface - Olivier Trédan; Philippe Gestin; Joël Langonné (Communication)
The authors investigate how organizational changes based on economic rationalism can affect the process of producing hyperlocal information and impact how things work on the periphery of regional daily press newsrooms in France. They identify new ways of disseminating local news on the fringes of established media and at a microlocal scale. Faced with restrictions imposed by management, key actors in the collection of “small news” are sometimes forced to sidestep newspapers in order to continue doing what they like to do: circulate information in rural areas.